Air pollution and cardiovascular disease: Can the Australian bushfires and global COVID‐19 pandemic of 2020 convince us to change our ways?. (9th June 2021) - Wolhuter, Kathryn; Arora, Manish; Kovacic, Jason C.
Abstract: Air pollution is a major global challenge for a multitude of reasons. As a specific concern, there is now compelling evidence demonstrating a causal relationship between exposure to airborne pollutants and the onset of cardiovascular disease (CVD). As such, reducing air pollution as a means to decrease cardiovascular morbidity and mortality should be a global health priority. This review provides an overview of the cardiovascular effects of air pollution and uses two major events of 2020—the Australian bushfires and COVID‐19 pandemic lockdown—to illustrate the relationship between air pollution and CVD. The bushfires highlight the substantial human and economic costs associated with elevations in air pollution. Conversely, the COVID‐19‐related lockdowns demonstrated that stringent measures are effective at reducing airborne pollutants, which in turn resulted in a potential reduction in cardiovascular events. Perhaps one positive to come out of 2020 will be the recognition that tough measures are effective at reducing air pollution and that these measures have the potential to stop thousands of deaths from CVD. Abstract : The 2019–2020 Australian bushfires, and the COVID‐19‐related lockdowns, highlight the intimate relationship between air pollution and cardiovascular disease. While the bushfires illustrate the dire effects of air pollution, the COVID‐19‐related lockdowns showed that stringent measures can reduce airborne pollutants, which in turn may reduce cardiovascular events.